A regenerated polyester dope colored sea-island composite fiber material and a preparation method thereof
Patent Information
- Application Number
- CN202511280677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-09-09
AI Technical Summary
原液着色技术虽可减少后期染整工序的污染,但将着色剂与功能助剂直接添加到再生聚酯中仍面临诸多挑战
其一:方案中通过引入9,10-二氢-9-氧杂-10-磷杂菲-10-氧化物(DOPO)结构,利用其P-H键与席夫碱C=N双键的亲核加成反应,将磷元素稳定结合到改性单体中,燃烧时催化形成致密炭层,有效隔绝热量和氧气;纳米二氧化硅作为无机增强相,高温下强化炭层稳定性,形成磷-硅协同阻燃体系,显著提高纤维极限氧指数、降低热释放速率,并减少阻燃剂用量,避免对力学性能和着色性的负面影响。此外,通过1,3-丙磺酸内酯与咪唑基团的开环反应引入磺酸基,赋予纤维持久亲水抗静电性;咪唑结构同时增强填料与聚酯基体的界面结合,提高了材料的耐磨性能,实现阻燃、亲水抗静电与力学增强的多功能协同。
Smart Images

Figure IMAGE_E17F7023-7F3A-40D0-96C5-4C5D9DEF52E3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite fiber technology, specifically, it relates to a recycled polyester dope-dyed island composite fiber material and its preparation method. Background Technology
[0002] Currently, the development and application of recycled polyester fibers is an important direction for achieving sustainable development in the chemical fiber industry. While solution dyeing technology can reduce pollution in later dyeing and finishing processes, directly adding colorants and functional auxiliaries to recycled polyester still faces many challenges. On the one hand, functional fillers (such as flame retardants) tend to aggregate in the matrix, affecting not only the stability of the spinning process and leading to a decline in fiber mechanical properties, but also causing uneven color and poor functional durability. On the other hand, conventionally blended modified fibers have limited functionality and cannot simultaneously meet the market's demand for multifunctional integrated fibers, such as those possessing comprehensive properties like flame retardancy, antistatic properties, high color fastness, and excellent abrasion resistance. Furthermore, existing technologies that simply add multiple auxiliaries to achieve multifunctionality often result in poor compatibility and weak interfacial bonding, further affecting the final quality and service life of the fiber.
[0003] Therefore, developing a method for preparing recycled polyester fibers that can achieve efficient filler dispersion, multifunctional synergy, and uniform color is of great practical significance. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a recycled polyester dope-dyed island composite fiber material and its preparation method.
[0005] The objective of this invention can be achieved through the following technical solutions: A method for preparing a recycled polyester dope-dyed island-of-sea composite fiber material includes the following steps: Step 1: Melt the recycled polyester chips, and add colorant and functional filler during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt the soluble polyester to obtain a marine component melt; Step 2: The colored filler dispersion melt and the sea component melt are co-spun through a sea-island type composite spinneret, cooled and wound to obtain sea-island composite fiber filaments; Step 3: The island composite fiber filaments are stretched and heat-set, then placed in a sodium hydroxide aqueous solution with a concentration of 3-8 wt% and a temperature of 80-95℃ for 20-40 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product.
[0006] In this scheme, two melts are co-spun using an island-type spinneret: one is a colored melt with recycled polyester as the "island" component and uniformly dispersed colorants and functional fillers, and the other is a soluble polyester melt as the "sea" component. After spinning, the fibers acquire stable mechanical properties through subsequent drawing and heat setting. Finally, the sea component is selectively hydrolyzed and dissolved using sodium hydroxide solution, while the colored island component is retained, thus obtaining an ultrafine fiber assembly that integrates color and function.
[0007] Ideally, the melting temperature of the recycled polyester chips is 270-285°C; and the melting temperature of the soluble polyester is 268-280°C.
[0008] In a more optimized manner, the raw materials for preparing the coloring filler dispersion melt include the following components: by weight, 80-100 parts of recycled polyester chips, 2-3 parts of colorant, and 5-8 parts of functional filler; wherein, the mass ratio of the coloring filler dispersion melt to the marine component melt is 1:(0.5-1).
[0009] In a more optimized manner, the preparation process of the functional filler is as follows: A1: Add nano-silica to an ethanol-water solution of 3-mercaptopropyltriethoxysilane, raise the temperature to 60-70℃, react for 3-4 hours, and after the reaction is complete, filter, wash, and dry to obtain mercapto-modified silica. A2: The modified monomer and photoinitiator were added to N,N-dimethylformamide, followed by the addition of mercapto-modified silica. The mixture was then irradiated under ultraviolet light for 40 minutes, filtered, washed, and dried to obtain the functional filler.
[0010] In the scheme, the first step (A1) involves a silane coupling agent hydrolysis-condensation reaction to hydrolyze the ethoxy group of 3-mercaptopropyltriethoxysilane into a silanol group, which then condenses with the silanol group on the surface of nano-silica to form a Si-O-Si covalent bond, thereby grafting thiol groups onto the silica surface to obtain thiolized silica. The second step (A2) utilizes ultraviolet light to initiate a free radical reaction. The photoinitiator generates free radicals that activate the sulfur-hydrogen bonds on the surface of thiolized silica, generating sulfur free radicals. These free radicals undergo a "thiol-alkene" click chemical addition reaction with the carbon-carbon double bonds in the modified monomer. Through surface grafting polymerization, the modified monomer is covalently immobilized onto the silica surface, ultimately obtaining an organic-inorganic hybrid functional filler.
[0011] In a more optimized manner, the raw materials for preparing the thiolized silica include the following components: by weight, 10-12 parts of nano-silica and 100-150 parts of an ethanol aqueous solution of 3-mercaptopropyltriethoxysilane; wherein the concentration of the ethanol aqueous solution of 3-mercaptopropyltriethoxysilane is 5 wt%; the raw materials for preparing the functional filler include the following components: by weight, 5-8 parts of modified monomer, 0.1-0.2 parts of photoinitiator, 100-200 parts of N,N-dimethylformamide, and 10-12 parts of thiolized silica.
[0012] In a more optimized manner, the preparation process of the modified monomer is as follows: S1: Mix p-hydroxybenzaldehyde, 3-bromopropene, and anhydrous ethanol, add potassium carbonate, raise the temperature to 78°C and reflux for 24 hours. After the reaction is complete, filter and remove the solvent by vacuum distillation to obtain intermediate A. S2: Intermediate A, N-(3-aminopropyl)imidazolium and N,N-dimethylformamide were mixed and reacted at 78°C for 24 h. After the reaction was completed, the reaction solution was allowed to stand for 3 h and filtered to obtain intermediate B. S3: Intermediate B, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and tetrahydrofuran were mixed and reacted at 70°C for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried. Then, it was transferred to acetonitrile, 1,3-propanesulfonic acid lactone was added, stirred and dissolved, and refluxed at 80°C for 24 h under a protective atmosphere. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by vacuum distillation, washed three times with cold diethyl ether, and dried under vacuum to obtain the modified monomer.
[0013] In the scheme, the first step (S1) is the Williamson ether synthesis reaction, where the phenolic hydroxyl group of p-hydroxybenzaldehyde is activated under alkaline conditions provided by potassium carbonate, and undergoes a nucleophilic attack on the carbon atom of 3-bromopropene, resulting in an SN2 nucleophilic substitution to generate intermediate A containing an allyl ether bond and an aldehyde group. The second step (S2) is an amine-aldehyde condensation reaction, where the aldehyde group of intermediate A undergoes a dehydration condensation with the primary amino group of N-(3-aminopropyl)imidazolium to form intermediate B with a Schiff base (C=N double bond) structure, while simultaneously introducing an imidazolium functional group. The third step (S3) is divided into two stages: first, the highly reactive pH bond in 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is used to nucleophilically add to the electron-deficient C=N double bond in intermediate B, introducing an organophosphorus flame-retardant structure; subsequently, the imidazolium nitrogen atom nucleophilically attacks the three-membered ring of 1,3-propanesulfonic acid lactone, resulting in a ring-opening reaction to generate a sulfonic acid-functionalized imidazolium salt. The specific synthesis process is shown below: In a more optimized manner, the raw materials for preparing intermediate A include the following components: by weight, 10-12 parts of p-hydroxybenzaldehyde, 8-10 parts of 3-bromopropene, 80-100 parts of anhydrous ethanol, and 10-15 parts of potassium carbonate.
[0014] In a more optimized manner, the raw materials for preparing intermediate B include the following components: by weight, 10-12 parts of intermediate A, 8-10 parts of N-(3-aminopropyl)imidazole, and 50-60 parts of N,N-dimethylformamide.
[0015] In a more optimized manner, the raw materials for preparing the modified monomer include the following components: by weight, 8-10 parts of intermediate B, 8-11 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 100-120 parts of tetrahydrofuran, 80-100 parts of acetonitrile, and 5-8 parts of 1,3-propanesulfonic acid lactone.
[0016] The beneficial effects of this invention are: Firstly, the scheme introduces a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) structure. Utilizing the nucleophilic addition reaction of its pH bond with the Schiff base C=N double bond, phosphorus is stably incorporated into the modified monomer. During combustion, this catalyzes the formation of a dense char layer, effectively isolating heat and oxygen. Nano-silica, as an inorganic reinforcing phase, enhances the stability of the char layer at high temperatures, forming a phosphorus-silicon synergistic flame-retardant system. This significantly improves the fiber's limiting oxygen index, reduces the heat release rate, and decreases the amount of flame retardant required, avoiding negative impacts on mechanical properties and colorability. Furthermore, the introduction of sulfonic acid groups through the ring-opening reaction of 1,3-propanesulfonic acid lactone with imidazole groups imparts durable hydrophilic and antistatic properties to the fiber. The imidazole structure simultaneously enhances the interfacial bonding between the filler and the polyester matrix, improving the material's wear resistance and achieving a multifunctional synergy of flame retardancy, hydrophilic antistatic properties, and mechanical reinforcement.
[0017] Secondly, the proposed solution employs an island-type composite spinning process, using recycled polyester containing colorants and functional fillers as the "island" component and soluble polyester as the "sea" component. After co-spinning, the fibers undergo stretching, heat setting, and alkali removal of the "sea" component to obtain an ultrafine fiber aggregate. This structure boasts a large specific surface area, fully exposing the flame-retardant and hydrophilic functional sites on the filler surface, significantly enhancing functional effects: accelerating char layer formation in terms of flame retardancy, and improving moisture absorption rate and capacity in terms of hydrophilic antistatic properties. Simultaneously, during the island-type spinning process, the "sea" component effectively inhibits the aggregation of fillers and colorants in the "island" component, ensuring uniform fiber coloring and stable filler dispersion, avoiding functional defects and degradation of mechanical properties, ultimately achieving a synergistic effect of refined structure, uniform color, and long-lasting functionality. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1: A method for preparing a recycled polyester dope-dyed island-of-sea composite fiber material, comprising the following steps: Step 1: Melt 80 parts of recycled polyester chips at 270℃, and add 2 parts of colorant (titanium dioxide) and 5 parts of functional filler during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt soluble polyester (purchased from Kanebo, Japan, model M-70, isophthalic acid content of 20mol%) at 268℃ to obtain marine component melt; Step 2: The colored filler dispersion melt and the marine component melt are co-spun through a sea-island type composite spinneret, cooled, and wound to obtain sea-island composite fiber filaments; the mass ratio of the colored filler dispersion melt to the marine component melt is 1:0.5; Step 3: The island composite fiber filaments are stretched and heat-set, then placed in a sodium hydroxide aqueous solution with a concentration of 3wt% and a temperature of 80℃ for 20 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product. The preparation process of the functional filler is as follows: A1: Add 10 parts of nano-silica to 100 parts of an ethanol aqueous solution of 3-mercaptopropyltriethoxysilane (concentration 5wt%), raise the temperature to 60℃, react for 3h, filter, wash, and dry to obtain mercapto-modified silica. A2: Add 5 parts of modified monomer and 0.1 parts of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) to 100 parts of N,N-dimethylformamide, then add 10 parts of mercapto-modified silica, irradiate under ultraviolet light for 40 min, filter, wash, and dry to obtain functional filler; The preparation process of the modified monomer is as follows: S1: Mix 10 parts of p-hydroxybenzaldehyde, 8 parts of 3-bromopropene, and 80 parts of anhydrous ethanol, add 10 parts of potassium carbonate, raise the temperature to 78℃ and reflux for 24 hours. After the reaction is completed, filter and remove the solvent by vacuum distillation to obtain intermediate A. S2: Mix 10 parts of intermediate A, 8 parts of N-(3-aminopropyl)imidazole and 50 parts of N,N-dimethylformamide, and react at 78°C for 24 hours. After the reaction is completed, let the reaction solution stand for 3 hours and filter to obtain intermediate B. S3: Mix 8 parts of intermediate B, 8 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 100 parts of tetrahydrofuran, and react at 70°C for 24 h. After the reaction is complete, filter, wash, and dry. Then transfer to 80 parts of acetonitrile, add 5 parts of 1,3-propanesulfonic acid lactone, stir to dissolve, and reflux at 80°C for 24 h under a protective atmosphere. After the reaction is complete, cool to room temperature, remove the solvent by vacuum distillation, wash 3 times with cold diethyl ether, and dry under vacuum to obtain the modified monomer.
[0020] Example 2: A method for preparing a recycled polyester dope-dyed island-of-sea composite fiber material, comprising the following steps: Step 1: Melt 100 parts of recycled polyester chips at 270℃, and add 3 parts of colorant (titanium dioxide) and 8 parts of functional filler during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt soluble polyester (purchased from Kanebo, Japan, model M-70, isophthalic acid content of 20mol%) at 268℃ to obtain marine component melt; Step 2: The colored filler dispersion melt and the marine component melt are co-spun through a sea-island type composite spinneret, cooled, and wound to obtain sea-island composite fiber filaments; the mass ratio of the colored filler dispersion melt to the marine component melt is 1:1. Step 3: The island composite fiber filaments are stretched and heat-set, then placed in an 8 wt% sodium hydroxide aqueous solution at 95°C for 40 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product. The preparation process of the functional filler is as follows: A1: 12 parts of nano silica were added to 150 parts of an ethanol aqueous solution of 3-mercaptopropyltriethoxysilane (concentration 5wt%), the temperature was raised to 70℃, and the reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain mercapto-modified silica. A2: Add 8 parts of modified monomer and 0.2 parts of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) to 200 parts of N,N-dimethylformamide, then add 12 parts of mercapto-modified silica, irradiate under ultraviolet light for 40 min, filter, wash, and dry to obtain functional filler; The preparation process of the modified monomer is as follows: S1: Mix 12 parts of p-hydroxybenzaldehyde, 10 parts of 3-bromopropene, and 100 parts of anhydrous ethanol, add 15 parts of potassium carbonate, raise the temperature to 78°C and reflux for 24 hours. After the reaction is complete, filter and remove the solvent by vacuum distillation to obtain intermediate A. S2: Mix 12 parts of intermediate A, 10 parts of N-(3-aminopropyl)imidazolium and 60 parts of N,N-dimethylformamide, and react at 78°C for 24 hours. After the reaction is completed, let the reaction solution stand for 3 hours and filter to obtain intermediate B. S3: Mix 10 parts of intermediate B, 11 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 120 parts of tetrahydrofuran, and react at 70°C for 24 h. After the reaction is complete, filter, wash, and dry. Then transfer to 100 parts of acetonitrile, add 8 parts of 1,3-propanesulfonic acid lactone, stir to dissolve, and reflux at 80°C for 24 h under a protective atmosphere. After the reaction is complete, cool to room temperature, remove the solvent by vacuum distillation, wash 3 times with cold diethyl ether, and dry under vacuum to obtain the modified monomer.
[0021] Example 3: A method for preparing a recycled polyester dope-dyed island-of-sea composite fiber material, comprising the following steps: Step 1: Melt 90 parts of recycled polyester chips at 270℃, and add 2.5 parts of colorant (titanium dioxide) and 6.5 parts of functional filler during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt soluble polyester (purchased from Kanebo, Japan, model M-70, isophthalic acid content of 20mol%) at 268℃ to obtain a marine component melt; Step 2: The colored filler dispersion melt and the marine component melt are co-spun through a sea-island type composite spinneret, cooled, and wound to obtain sea-island composite fiber filaments; the mass ratio of the colored filler dispersion melt to the marine component melt is 1:0.75; Step 3: The island composite fiber filaments are stretched and heat-set, then placed in a sodium hydroxide aqueous solution with a concentration of 5.5 wt% and a temperature of 87.5℃ for 30 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product. The preparation process of the functional filler is as follows: A1: 11 parts of nano-silica were added to 125 parts of an ethanol aqueous solution of 3-mercaptopropyltriethoxysilane (concentration 5wt%), the temperature was raised to 65℃, and the reaction was carried out for 3.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain mercapto-modified silica. A2: 6.5 parts of modified monomer and 0.15 parts of photoinitiator (2,2-dimethoxy-2-phenylacetophenone) were added to 150 parts of N,N-dimethylformamide, followed by 11 parts of mercapto-modified silica. The mixture was irradiated under ultraviolet light for 40 min, filtered, washed, and dried to obtain the functional filler. The preparation process of the modified monomer is as follows: S1: Mix 11 parts of p-hydroxybenzaldehyde, 9 parts of 3-bromopropene, and 90 parts of anhydrous ethanol, add 12.5 parts of potassium carbonate, raise the temperature to 78°C and reflux for 24 hours. After the reaction is completed, filter and remove the solvent by vacuum distillation to obtain intermediate A. S2: Mix 11 parts of intermediate A, 9 parts of N-(3-aminopropyl)imidazole and 55 parts of N,N-dimethylformamide, and react at 78°C for 24 hours. After the reaction is completed, let the reaction solution stand for 3 hours and filter to obtain intermediate B. S3: 9 parts of intermediate B, 9.5 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 110 parts of tetrahydrofuran were mixed and reacted at 70°C for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried. Then, it was transferred to 90 parts of acetonitrile, and 6.5 parts of 1,3-propanesulfonic acid lactone were added. The mixture was stirred to dissolve and refluxed at 80°C for 24 h under a protective atmosphere. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by vacuum distillation, and the mixture was washed three times with cold diethyl ether and dried under vacuum to obtain the modified monomer.
[0022] Comparative Example 1: No functional fillers were added, as detailed below: Step 1: Melt 90 parts of recycled polyester chips at 270℃, and add 2.5 parts of colorant (titanium dioxide) during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt soluble polyester (purchased from Kanebo, Japan, model M-70, isophthalic acid content of 20mol%) at 268℃ to obtain marine component melt; Step 2: The colored filler dispersion melt and the marine component melt are co-spun through a sea-island type composite spinneret, cooled, and wound to obtain sea-island composite fiber filaments; the mass ratio of the colored filler dispersion melt to the marine component melt is 1:0.75; Step 3: The island composite fiber filaments are stretched and heat-set, then placed in a sodium hydroxide aqueous solution with a concentration of 5.5 wt% and a temperature of 87.5℃ for 30 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product.
[0023] Comparative Example 2: Functional fillers do not introduce functional monomers, as detailed below: Step 1: Melt 90 parts of recycled polyester chips at 270℃, and add 2.5 parts of colorant (titanium dioxide) and 6.5 parts of functional filler during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt soluble polyester (purchased from Kanebo, Japan, model M-70, isophthalic acid content of 20mol%) at 268℃ to obtain a marine component melt; Step 2: The colored filler dispersion melt and the marine component melt are co-spun through a sea-island type composite spinneret, cooled, and wound to obtain sea-island composite fiber filaments; the mass ratio of the colored filler dispersion melt to the marine component melt is 1:0.75; Step 3: The island composite fiber filaments are stretched and heat-set, then placed in a sodium hydroxide aqueous solution with a concentration of 5.5 wt% and a temperature of 87.5℃ for 30 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product. The preparation process of the functional filler is as follows: 11 parts of nano-silica are added to 125 parts of ethanol aqueous solution of 3-mercaptopropyltriethoxysilane (concentration of 5wt%), the temperature is raised to 65℃, and the reaction is carried out for 3.5h. After the reaction is completed, the mixture is filtered, washed, and dried to obtain mercapto-modified silica.
[0024] Testing and experimentation: (1) The volume resistivity of the finished products obtained in the examples and comparative examples was tested using a YG321 fiber resistivity meter produced by Nantong Sansi Electromechanical Technology Co., Ltd. (2) The limiting oxygen index of the finished products obtained in the examples and comparative examples was measured using an oxygen index instrument in accordance with standard GB / T2406-93. (3) The finished products obtained from the examples and comparative examples are woven into fabrics, and the abrasion resistance is tested using an abrasion tester according to standard GB / T21196.3-2007. The specific operation is as follows: the fabric to be tested is cut into a circle with a diameter of 38±0.5mm, and standard 600-grit wet sandpaper is used as abrasive (the abrasive is replaced once after 5000 abrasion times). The pressure is 9kPa, and the abrasion resistance ends when two independent yarns of the fabric break. The number of abrasion times is recorded. The obtained data is shown in Table 1: Table 1 Volume resistivity (Ω·cm) <![CDATA[6.5×10 8 ]]> <![CDATA[5.1×10 8 ]]> <![CDATA[4.2×10 8 ]]> <![CDATA[8.3×10 12 ]]> <![CDATA[3.5×10 10 ]]> Limiting oxygen index (%) 30.5 31.2 32.3 21.4 24.5 Wear resistance times 7150 7214 7235 3215 4134 Conclusion: A comparison of the test data from the examples and comparative examples shows that the recycled polyester dope-dyed island composite fiber material prepared by the present invention exhibits significant advantages in antistatic properties, flame retardancy, and wear resistance.
[0025] The volume resistivity of Examples 1 to 3 is all above 10. 8 The value is on the order of Ω·cm, far lower than that of Comparative Example 1 (10). 12 ) and Comparative Example 2 (10 10The results show that the fiber exhibits excellent antistatic properties after the introduction of functional fillers; the limiting oxygen index exceeds 30%, significantly higher than Comparative Example 1 (21.4%) and Comparative Example 2 (24.5%), indicating that the material possesses good flame retardant properties; the abrasion resistance is also significantly improved, with all examples exceeding 7000 cycles, far exceeding Comparative Example 1 (3215 cycles) and Comparative Example 2 (4134 cycles), indicating that the introduction of functional fillers enhances the abrasion resistance of the fiber. In summary, this invention successfully prepares a multifunctional recycled polyester fiber material with uniform coloring, high-efficiency flame retardancy, long-lasting antistatic properties, and enhanced abrasion resistance through the synergistic effect of island-sea composite spinning process and functional fillers, showing promising application prospects.
[0026] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0027] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a recycled polyester dope-dyed island-of-sea composite fiber material, characterized in that, Includes the following steps: Step 1: Melt the recycled polyester chips, and add colorant and functional filler during the melting process, mix evenly to obtain a colored and filled dispersion melt; melt the soluble polyester to obtain a marine component melt; Step 2: The colored filler dispersion melt and the sea component melt are co-spun through a sea-island type composite spinneret, cooled and wound to obtain sea-island composite fiber filaments; Step 3: The island composite fiber filaments are stretched and heat-set, then placed in a sodium hydroxide aqueous solution with a concentration of 3-8 wt% and a temperature of 80-95℃ for 20-40 minutes. After that, they are neutralized, washed, dried and crimped to obtain the finished product. The preparation process of the functional filler is as follows: A1: Add nano-silica to an ethanol-water solution of 3-mercaptopropyltriethoxysilane, raise the temperature to 60-70℃, react for 3-4 hours, and after the reaction is complete, filter, wash, and dry to obtain mercapto-modified silica. A2: The modified monomer and photoinitiator were added to N,N-dimethylformamide, followed by the addition of mercapto-modified silica. The mixture was irradiated under ultraviolet light for 40 min, filtered, washed, and dried to obtain the functional filler. The preparation process of the modified monomer is as follows: S1: Mix p-hydroxybenzaldehyde, 3-bromopropene, and anhydrous ethanol, add potassium carbonate, raise the temperature to 78°C and reflux for 24 hours. After the reaction is complete, filter and remove the solvent by vacuum distillation to obtain intermediate A. S2: Intermediate A, N-(3-aminopropyl)imidazolium and N,N-dimethylformamide were mixed and reacted at 78°C for 24 h. After the reaction was completed, the reaction solution was allowed to stand for 3 h and filtered to obtain intermediate B. S3: Intermediate B, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and tetrahydrofuran were mixed and reacted at 70°C for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried. Then, it was transferred to acetonitrile, 1,3-propanesulfonic acid lactone was added, stirred and dissolved, and refluxed at 80°C for 24 h under a protective atmosphere. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by vacuum distillation, washed three times with cold diethyl ether, and dried under vacuum to obtain the modified monomer.
2. The method for preparing a recycled polyester dope-dyed island-sea composite fiber material according to claim 1, characterized in that, The melting temperature of the recycled polyester chips is 270-285℃; the melting temperature of the soluble polyester is 268-280℃.
3. The method for preparing a recycled polyester dope-dyed island-sea composite fiber material according to claim 1, characterized in that, The raw materials for preparing the colored filler dispersion melt include the following components: by weight, 80-100 parts of recycled polyester chips, 2-3 parts of colorant, and 5-8 parts of functional filler; wherein, the mass ratio of the colored filler dispersion melt to the marine component melt is 1:(0.5-1).
4. The method for preparing a recycled polyester dope-dyed island-sea composite fiber material according to claim 1, characterized in that, The raw materials for preparing the thiolized silica include the following components: by weight, 10-12 parts of nano silica and 100-150 parts of an ethanol aqueous solution of 3-mercaptopropyltriethoxysilane; wherein the concentration of the ethanol aqueous solution of 3-mercaptopropyltriethoxysilane is 5 wt%; the raw materials for preparing the functional filler include the following components: by weight, 5-8 parts of modified monomer, 0.1-0.2 parts of photoinitiator, 100-200 parts of N,N-dimethylformamide, and 10-12 parts of thiolized silica.
5. The method for preparing a recycled polyester dope-dyed island-sea composite fiber material according to claim 1, characterized in that, The raw materials for preparing intermediate A include the following components: by weight, 10-12 parts of p-hydroxybenzaldehyde, 8-10 parts of 3-bromopropene, 80-100 parts of anhydrous ethanol, and 10-15 parts of potassium carbonate.
6. The method for preparing a recycled polyester dope-dyed island-sea composite fiber material according to claim 1, characterized in that, The raw materials for preparing intermediate B include the following components: by weight, 10-12 parts intermediate A, 8-10 parts N-(3-aminopropyl)imidazole, and 50-60 parts N,N-dimethylformamide.
7. The method for preparing a recycled polyester dope-dyed island-sea composite fiber material according to claim 1, characterized in that, The raw materials for preparing the modified monomer include the following components: by weight, 8-10 parts intermediate B, 8-11 parts 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 100-120 parts tetrahydrofuran, 80-100 parts acetonitrile, and 5-8 parts 1,3-propanesulfonic acid lactone.
8. The finished product obtained by the preparation method of recycled polyester dope-dyed island composite fiber material according to any one of claims 1-7.
Citation Information
Patent Citations
Stock solution dyed black sea-island fiber
CN106987923A
Flame-retardant superfine polyester and nylon island fiber and manufacturing method thereof
CN109355733A
High-wear-resistance EPDM rubber material and preparation method thereof
CN119161672A
Conductive ink for ink-jet printing and preparation method thereof
CN120118562A